Andersen on financial planning : how to increase and preserve your money no matter how much you make - Andersen, Carl E. (Homewood, Ill. : Dow Jones-Irwin, 1986)
This book is a consumer's guide to financial planning that explain what it is, how it works, who needs it and why. It further helps you safeguard your financial health the same way regular checkups ensure your physical well-being.
Includes index.
hza 18/09/2018
Loans
Keywords: Finance, Personal; Financial planners